Instructional Strategies of Islamic Creed and Ethics (Aqidah Akhlak) Teachers in Fostering Students' Religious and Social Attitudes at MAN 3 East Seram - Edi Rumau (IAIN Ambon, 2025)
his study aims to describe the learning strategies employed by Akidah Akhlak teachers in fostering students’ religious and social attitudes at MAN 3 East Seram. The research used a qualitative approach with a field research design. The participants consisted of the principal, Akidah Akhlak teachers, and students. Data were collected through observation, interviews, and documentation. Data analysis followed Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The findings revealed that teachers implemented various learning strategies such as role modeling, habituation, advice-giving, group discussions, contextual learning, and reinforcement through religious activities. These strategies contributed to developing students’ religious attitudes, including discipline in worship, honesty, responsibility, and social awareness. Supporting factors included the school environment, teacher involvement, and structured religious programs. Inhibiting factors included external environmental influences and uncontrolled social media use.